2022
DOI: 10.1007/s10311-022-01520-y
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed for climate mitigation, wastewater treatment, bioenergy, bioplastic, biochar, food, pharmaceuticals, and cosmetics: a review

Abstract: The development and recycling of biomass production can partly solve issues of energy, climate change, population growth, food and feed shortages, and environmental pollution. For instance, the use of seaweeds as feedstocks can reduce our reliance on fossil fuel resources, ensure the synthesis of cost-effective and eco-friendly products and biofuels, and develop sustainable biorefinery processes. Nonetheless, seaweeds use in several biorefineries is still in the infancy stage compared to terrestrial plants-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 364 publications
0
34
0
Order By: Relevance
“…Biodegradable plastics, known as bioplastics, offer a promising solution for replacing conventional microplastics in various applications (Farghali et al 2022b, Dhaka et al 2022). These plastics have already been used in food and pharmaceutical packaging materials, such as polyhydroxyalkanoates, and in agriculture and horticulture as mulching films for soil and crop protection (Filiciotto and Rothenberg 2021;Zhang et al 2020).…”
Section: Using Biodegradable Plasticsmentioning
confidence: 99%
“…Biodegradable plastics, known as bioplastics, offer a promising solution for replacing conventional microplastics in various applications (Farghali et al 2022b, Dhaka et al 2022). These plastics have already been used in food and pharmaceutical packaging materials, such as polyhydroxyalkanoates, and in agriculture and horticulture as mulching films for soil and crop protection (Filiciotto and Rothenberg 2021;Zhang et al 2020).…”
Section: Using Biodegradable Plasticsmentioning
confidence: 99%
“…Bioplastics are innovative bio-based plastic polymers (Farghali et al 2022). Bioplastics are divided into three main types, (1) biodegradable and bio-based materials represented by starch-based polymers; (2) biodegradable and petroleumderived materials; (3) non-biodegradable bio-based materials (Abraham et al 2021).…”
Section: Bioplasticmentioning
confidence: 99%
“…A 2022 state of the art review reported on a wide range of utilisations and discussed bene ts across 'climate change mitigation and environmental sustainability, food consumption, animal feed additives, sh diets, bioplastic production, biofertilisers, biochar production, carbon sequestration tools, crop enhancers, antimicrobials, anti-in ammatory, anticancer, contraceptive, cosmetics, and skin care agents' (Farghali et al, 2022). Whilst presenting a comprehensive academic overview, there is both a notable absence and lack of enquiry into the potential uses of seaweeds in construction.…”
Section: Gaps and Opportunitiesmentioning
confidence: 99%